(3CUhd GdCMcGe aj eYQaI GdMdGd ef GdMQGes - (3GdeJhcd Ydj Gddg CMeO Hf SdjeGf GdgGOj,J (B566 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdcHjQ GdeJYGdi, Pi GdYXeI hGdLdGd , hGdef hGdCaVGd SQjY GdMSGH s
(3BNQgG (B:s
(3hdGSge ddHZGd hGdMejQ hGdLeGd , dCfg de jQO Yf GdfHi Udi Gddg Ydjg hSde Gfg CSge HTF efgG Je GdcJGH hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3Ydi MhGTjgG JUMjMGJ hJYdjbGJ s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis